Neonatal mortality and contraceptive utilization following abortion restriction in the Dominican Republic: A difference-in-differences analysis - Ishola, Foluso; McKinnon, Britt; Yang, Seungmi; Nandi, Arijit (Social science & medicine (1982), 2025)
In 2009, the Dominican Republic's Constitutional Assembly banned abortion under all circumstances, including cases of rape and/or situations in which the mother's health is at risk. Abortion policies have the potential to influence access to reproductive and neonatal health services, health outcomes, and health equity. In this study, we utilized a difference-in-differences approach to evaluate the association between the 2009 abortion reform in the Dominican Republic and neonatal mortality and modern contraceptive utilization. We harmonized data from Demographic and Health Surveys (DHS) and Multiple Indicator Cluster Surveys (MICS) between 1999 and 2019 to assemble a panel of 792,165 live births across 17 countries for analyses of neonatal mortality and 417,110 women ages 15–49 across 8 countries for analyses of modern contraceptive use. We compared outcome trajectories in the Dominican Republic to a group of control countries that did not change their abortion policies during the study period and are assumed to represent the counterfactual. Fixed effects for country and year were included to control for unobserved time-invariant confounders that varied across countries and temporal trends that were shared across countries, respectively. We also assessed for heterogeneity by household wealth, rural residency, and educational attainment through a stratified analysis. Over the study period, the rate of neonatal mortality was 27.0 per 1,000 live births and there were 39 per 100 women reporting use of modern contraceptives. Abortion restriction was associated with an additional 6.3 (95 % CI = 2.1, 10.5) neonatal deaths per 1,000 live births and a 9.6 (95 % CI = 4.2, 15.0) percentage-point decrease in modern contraceptive use. Estimates were robust to adjustment for individual, household, and country-level characteristics. However, there is possibility of residual confounding by unmeasured time-varying confounders, such as concomitant policy changes or interventions. Further research into how restrictive abortion policies compound racial, ethnic, and socioeconomic inequities is needed. •There was a shift to a more restrictive abortion context in Dominican Republic in 2009.•Abortion restriction was associated with poorer neonatal outcomes.•There was also reduction in modern contraceptive use among women of reproductive age.